Student activities: Cyber Security SIG - Mansor, Hafizah (2022)
Cyber Security Special Interest Group (SIG), IIUM is established with the objectives of nurturing students and IIUM community with cybersecurity knowledge and awareness. Our activities range from awareness programs, and technical workshops to cater the different needs and interests of students. We are very grateful to Kulliyyah of ICT (KICT) and Centre of Excellence in Cyber Security (CoExCyS) who have been very supportive to our programmes.